Defining Friction Force: A Proposed Solution to a Textbook Problem - Fatih Develi; Bahadir Namdar (Seyit Ahmet Kıray, 2019)
Scientific concepts are the building blocks of scientific thought and science communication. Therefore, to achieve scientific literacy it is necessary to construct and define the concepts accurately. In this study, the concept of friction force, which is frequently encountered in science textbooks, is discussed. The explanations of the concept in science textbooks have been found to be inadequate in effectively explaining several situations. To address this issue, this study aimed to examine the concept of friction force in the textbooks and to propose a more comprehensive definition. The study was conducted using the document analysis method. A total of 26 resource books (11 university physics textbooks, 4 science-term glossaries, 2 secondary school physics textbooks, 6 middle school science textbooks, and 3 popular science textbooks) were analyzed in the study. Several inconsistencies in the explanations for the concept of friction force were found. Based on the analysis, a more comprehensive definition was proposed to fully and consistently explain the effects and the direction of friction force.